Musculoskeletal injury in paddle sport athletes - Griffin, A. R.; Perriman, D. M.; Neeman, T. M.; Smith, P. N. (Clinical Journal of Sport Medicine, 2020)
Kayak racing has been an Olympic sport since 1936. The sport is evolving with the introduction of ocean skis and stand-up-paddle boards (SUP). Musculoskeletal injury incidence surveys have been conducted for ultra-marathon events, but no data have been published for other racing formats. Objective: To identify and compare the rates and types of injuries sustained by paddling athletes as a function of discipline and training parameters in Sprint, Marathon, Ultra-Marathon, and Ocean events. Methods: Competitors from 6 kayak and/or ocean surf-ski races in Australia were surveyed. Before each race, competitors were asked to complete a questionnaire. The questionnaire investigated paddling-related injuries over the previous 5 years, athlete morphology, flexibility, equipment and its setup, training volume, and environment. Results: Five hundred eighty-three competitors were surveyed. Disciplines included 173 racing-kayak (K1), 202 touring-kayak, 146 ocean-skis, 42 SUP, and 20 other. The top 5 paddling-related injuries were shoulder (31%), low back (23.5%), wrist (16.5%), neck (13.7%), and elbow (11.0%). The highest percentage of injury was found in K1 paddlers for shoulder (40.5%), SUP for low back (33.3%), and ocean-ski for wrist (22.6%). After controlling for on-water training hours, the relative risk (RR) of wrist injury was significantly increased in ocean-ski paddlers (1.86) and in paddlers with decreased flexibility (1.53-1.83). Relative risk of shoulder and low-back injury was significantly increased in athletes with lower training volumes (1.82-2.07). Younger athletes had lower RR of wrist and shoulder injury (0.58-0.62).